A Study on planning and evaluation system for carbon-neutral green city construction - KIM, Byoungki (KDI School, 2024)
Climate change is emerging as the biggest problem threatening human existence around the world. Nearly half of humanity, 3.5 billion people, are currently living in urban areas, and more than 5 billion people are expected to live in cities by 2030. Cities account for 60-80% of energy consumption and 75% of carbon emissions used by humans, and to realize carbon neutrality in the era of climate change, many changes must be made around urban areas. A carbon-neutral city is a city that minimizes fossil energy dependence and energy consumption to curb carbon emissions caused by fossil energy use and neutralizes or zero carbon emissions inevitably generated by economic and social activities through continuous use of renewable energy sources and maximization of energy efficiency (Kim, Choi, 2011). Realizing carbon neutrality in cities, which account for the largest portion of carbon emissions, is a keyword that clearly shows that carbon neutrality is the first thing to consider to realize carbon neutrality in the era of climate change. This study aims to examine domestic and foreign cases centered on cities to realize carbon neutrality and to examine the essential components to be considered to create a carbon-neutral city and what performance evaluation should be conducted after introducing them. I hope that this study will help realize carbon-neutral cities in Korea in the future by awakening the necessity of carbon neutrality centered on cities.
Thesis(Master) -- KDI School: Master of Public Management, 2024
Keywords: City planning--Environmental aspects; Sustainable urban development